Approximate Analytical Solution of Nonlinear Reaction's Diffusion Equation at Conducting Polymer Ultramicroelectrodes. (27th March 2012) - Shanmugarajan, Anitha; Alwarappan, Subbiah; Lakshmanan, Rajendran
Abstract : A theoretical model of reaction/diffusion within conducting polymer microelectrodes is discussed. The model is based on the steady-state diffusion equation containing a nonlinear term related to the Michaelis-Menten kinetic of the enzymatic reaction. An analytical expression pertaining to the concentration of substrate and current is obtained using homotopy perturbation method for all values of diffusion and the saturation parameter. The substrate concentration profile and current response can be used in a large range of concentrations including the non-linear contributions. These approximate analytical results were found to be in good agreement with the previously reported limiting case results.